Pengaruh Sistem E-Kinerja Dan Teknologi Informasi Terhadap Kompetensi Personil Pada Dinas Penelitian Dan Pengembangan TNI Angkatan Laut - Bambang Hariyanto; Bambang Suharjo; Hanjar K (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to evaluate the impact of the E-Performance System and Information Technology on personnel competence at the Research and Development Department of the Indonesian Navy. Using the Partial Least Square (PLS) method, the research findings indicate that both variables have a significant and positive influence on improving personnel competence. The E-Performance System has been shown to enhance the efficiency and effectiveness of performance monitoring and evaluation, while Information Technology facilitates faster access and better collaboration. The implementation of these two systems not only improves individual performance but also supports the overall achievement of organizational goals. Challenges encountered in the implementation of these systems, such as resistance to change and lack of training, can be addressed through appropriate strategies, including continuous training and adequate technical support. In conclusion, the integration of the E-Performance System and Information Technology is key to enhancing personnel competence and maintaining organizational competitiveness amid the evolving technological landscape.